Apple pie ABC - Murray, Alison (Orchard, 2011)
An utterly delicious introduction to the alphabet from the cutest pup you're likely to find! This traditional verse is retold with wit, filled with charm and illustrated with tremendous style by an exciting debut artist
First published: 2010
Keywords: Puppies / Pictorial works / Juvenile fiction; English language / Alphabet / Pictorial works / Juvenile fiction; Children's stories / Pictorial works; Englisch; Ungehorsam; Alphabet; Mädchen; Hund; Apfelkuchen; Bilderbuch